Self-rated health and its related influencing factors among emergency department physicians: a national cross-sectional study - Peng, Ke; Jiang, Jingjing; Jiang, Nan; An, Rongrong; Zheng, Jianwei; Yan, Shijiao (Frontiers in Public Health, 2023)
Background Protecting and improving the personal health of healthcare workers is critical to improving the efficiency and quality of care. To effectively meet the needs of the emergency service system, emergency physicians need to be in a good state of health. However, due to the special characteristics of work in the emergency department, emergency physicians have to face various psychosocial pressures, which may bring them physical and mental distress. Therefore, this study aims to explore the emergency physicians' self-rated health status and its related factors, to provide an empirical study for the improvement of emergency physicians' self-rated health status. Method A cross-sectional survey of emergency physicians was conducted in China between July and August 2018. The questionnaires contained items on demographic characteristics, behavioral lifestyle and job-related factors, as well as self-rated health. The generalized ordinal logistic model was used to identify related factors of emergency physicians' self-rated health status. Results Only 14.4% of Chinese emergency physicians considered themselves in good health status. Results showed that emergency physicians who never exercised (β = 0.76, p < 0.001) and exercised <2 times per week (β = 0.34, p < 0.001) were more likely to report poor health status. In addition, emergency physicians with good sleep quality (β = −3.84, p < 0.001), fewer night work shifts (β = −0.47, p < 0.001), less frequency of visiting patients (β = −0.33, p < 0.001), never suffered the workplace violence (β = −0.47, p < 0.001) and never perceived effort-reward imbalance (β = −0.68, p < 0.001) were more likely to report good self-rated health. Conclusion Chinese emergency physicians' self-rated health status was not optimistic. Self-rated health is associated with multiple domains of work-related factors and personal lifestyle. Feasible measures should be taken to improve the working environment of emergency physicians, develop acceptable shift schedules for employees, monitor and maintain the health status of emergency department physicians.